Effect of Chlorogenic Acid (5-Caffeoylquinic Acid) Isolated from Baccharis oxyodonta on the Structure and Pharmacological Activities of Secretory Phospholipase A2 from Crotalus durissus terrificus - Toyama, Daniela O. [UNESP]; Ferreira, Marcelo J. P.; Romoff, Paulete; Favero, Oriana A.; Gaeta, Henrique H. [UNESP]; Toyama, Marcos H. [UNESP] (Hindawi Publishing Corporation, 2014)
The aim of this paper was to investigate the effect of chlorogenic acid (5-caffeoylquinic acid, 5CQA), isolated from Baccharis oxyodonta, on the structure and pharmacological effect of secretory phospholipase A2 (sPLA2) from Crotalus durissus terrificus. All in vitro and in vivo experiments were conducted using a purified sPLA2 compared under the same experimental conditions with sPLA2 : 5CQA. 5CQA induced several discrete modifications in the secondary structure and the hydrophobic characteristics of native sPLA2 that induced slight changes in the alpha-helical content, increase in the randomcoil structure, and decrease of fluorescence of native sPLA2. Moreover, 5CQA significantly decreased the enzymatic activity and the oedema and myonecrosis induced by native sPLA2. As the catalytic activity of sPLA2 plays an important role in several of its biological and pharmacological properties, antibacterial activity was used to confirm the decrease in its enzymatic activity by 5CQA, which induced massive bacterial cell destruction. We found that 5CQA specifically abolished the enzymatic activity of sPLA2 and induced discrete protein unfolding that mainly involved the pharmacological site of sPLA2. These results showed the potential application of 5CQA in the snake poisoning treatment and modulation of the pathological effect of inflammation induced by secretory PLA2.